RUPERT BROOKE AND PAUL NASH: THE POET AND THE PAINTER OF WORLD WAR I - Monika; Meena, Ramesh Chand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper discusses the artistic and aesthetic genius of the poet Rupert Brooke and the painter Paul Nash in their respective areas. Rupert Brooke is acclaimed as one of the finest representative war poets of the time. During the modern writings of fragmented, free, dense and long verses Brooke adapted the sonnet to share war experiences. These sonnets by Brooke have been placed among the supreme expressions of English patriotism and the few notable poems produced by the Great War. His best five war sonnets (1914) are entitled– ‘Peace’, ‘Safety’, ‘The Dead’, ’The Dead’ and ‘The Soldier’. Paul Nash was a British surrealist painter and war artist, photographer and writer. In 1917 he was officially announced as a war artist. Nash found his inspiration in landscape from the elements of ancient history. His artworks during the Great War are considered the most iconic images of conflict. Nash’s works are often believed to be influenced by the Vorticist movement. The medium he used were water colour, ink and chalk, etc. His notable works are- ‘We are Making a New World’ (1918), ‘The Menin Road’ (1918), ‘Spring in the Trenches’ (1918), ‘Wire’ (1919), etc. How successfully has their artistic vision made people able to understand the need of the future world? The Relevance of these artistic and literary pieces for today’s human race, etc. will be the focal points of discussion. The paper will be prepared with a comparative and analytical study of the subject matter.